2009
DOI: 10.1111/j.1365-294x.2009.04236.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed banks cause elevated generation times and effective population sizes of Arabidopsis thaliana in northern Europe

Abstract: It is commonly found that effective population sizes of natural populations are much smaller than census sizes of plants and animals. However, theoretical studies have shown that factors rarely investigated empirically, like seed banks in plants and diapause in animals, may have profound influence on effective sizes. Here we investigate whether the presence of seed banks can explain the relatively high genetic variability observed in northern European Arabidopsis thaliana populations with small census sizes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
106
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(119 citation statements)
references
References 93 publications
8
106
3
2
Order By: Relevance
“…This is evidenced by the observation that only about 66% of maximum LD is encountered in sampled microsatellite loci. Such levels are frequently found even in populations of the highly selfing model angiosperm Arabidopsis thaliana (Lundemo et al, 2009) and does not necessarily imply very recent or frequent recombination within populations.…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by the observation that only about 66% of maximum LD is encountered in sampled microsatellite loci. Such levels are frequently found even in populations of the highly selfing model angiosperm Arabidopsis thaliana (Lundemo et al, 2009) and does not necessarily imply very recent or frequent recombination within populations.…”
Section: Discussionmentioning
confidence: 99%
“…Local estimates of N e , based on approximately 100 SNP markers in A. thaliana from Scandinavia, suggest that N e may be more commonly of the order of 250-2500 [87].…”
Section: Mutation and Driftmentioning
confidence: 99%
“…In 2012, another survey was performed that identified seven new demes and found that nine demes identified in 2011 had disappeared because of human disturbance (five demes) or unknown causes (four demes; Supplemental Table S2). It is possible that some of the demes that were not reidentified in 2011 and 2012 may reestablish themselves from the soil seed bank if it remains intact, because seeds shed at least 3 years previously can remain viable (Lundemo et al, 2009;Picó, 2012;Falahati-Anbaran et al, 2014). In total, 44 demes detected in 2012 were sampled: 20 from coastal areas and 24 in adjacent inland areas (Fig.…”
Section: Identification Of Coastal and Adjacent Inland Populations Ofmentioning
confidence: 99%